(3SjGSGJ EOGQI eNGWQ SYQ GdUQa eY CSFdI JbjjejI hELGHI fehPLjIs - (3Hf YHO GdYRjR(B, (3SejQs ((3GdLRGFQs (3OGQ CLjGd GdQbej s, 2024)
(3jMJhj GdcJGH Ydi CQHYI eMGhQ , aGdeMhQ GdChd jVe eaGgje YGeI dSYQ GdUQa hShb GdUQa, hGdKGfj jJMOK Yf CfXeI GdUQa hGdfXQjGJ GdeMOOI dSYQ GdUQa CeG GdKGdK hGdQGHY ajVe SGSGJ heNGWQ SYQ GdUQa hJbfjGJ JZWjI eNGWQ SYQ GdUQa HeG ajgG CSFdI JbjjejI hELGHGJ fehPLjI (B.s
Keywords: (3EOGQI GdeNGWQs; (3GdCShGb GdeGdjIs; (3SYQ GdUQas